1966
DOI: 10.5796/jesj.34.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Solution of Cadmium in Molten Cadmium Chloride. II. Effects of Added Chlorides on the Solubility of Cadmium in Molten Chloride

Abstract: In order to study the effects of added chlorides on the solubility of cadmium metal in the molten cadmium chloride, its solubility in CdC1 2-KCl-AICl 3 mixtures was determined by measuring the EMF of C / Cd, CdC1 2-KCI-AlC1/ / CdC1 2-KCI-AlC13, Cd(sat.) / C cells. For the Cd-CdC1 2 s ystem, solubility limits were determined as 0.156 (molar fraction) at 600°C and 0.189 at 7 40°<:;:. It was found that these values increased with the addition of A1Cl 3-rich chloride mixtures, but decreased with the addition of KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Here the value at 723 K is 2.463 Ϯ 0.001 V vs Li + /Li. This result indicates that the previous study by Kanzaki and Takahashi,11 in which the standard electrode potential was determined by the measurement of emf using a platinum electrode, was more precise than the determination from the solubility of refractory metal oxides in the melt reported by Masuko et al 7 although the influence of a mixed potential was not completely avoided on a platinum electrode as described in the Introduction. It is also suggested that our previous study, estimated from the Li 2 O solubility, 12 is almost precise.…”
Section: ͓10͔mentioning
confidence: 66%
See 2 more Smart Citations
“…Here the value at 723 K is 2.463 Ϯ 0.001 V vs Li + /Li. This result indicates that the previous study by Kanzaki and Takahashi,11 in which the standard electrode potential was determined by the measurement of emf using a platinum electrode, was more precise than the determination from the solubility of refractory metal oxides in the melt reported by Masuko et al 7 although the influence of a mixed potential was not completely avoided on a platinum electrode as described in the Introduction. It is also suggested that our previous study, estimated from the Li 2 O solubility, 12 is almost precise.…”
Section: ͓10͔mentioning
confidence: 66%
“…It affects the passivation phenomena on the surface of the produced metals 5 and plays an important role in acid-base reactions. 6,7 To understand the chemical and electrochemical behaviors of oxide ion in molten chlorides, it is necessary to determine the thermodynamic quantities of oxide ion such as chemical potentials in molten chlorides.…”
mentioning
confidence: 99%
See 1 more Smart Citation